Isothermic Adsorption Study of Nitrate Ion Adsorption in Bioethanol Waste Using Quaternary Ammonium Polymer - Amrillah, Nafira Alfi Zaini; Rahayu, Aster; Dhias Cahya Hakika; Vivi Sisca; Veranica; Firda Mahira Alfiata Chusna; Lia Anggresani; Lee Wah Lim (Universitas Nusa Bangsa, 2025)
The global shift towards renewable energy sources has led to a significant increase in bioethanol production, particularly from sugar mills. Despite being an environmentally friendly alternative to fossil fuels, bioethanol production produces large amounts of waste containing dangerous contaminants such as nitrate ions (NO₃⁻). These contaminants pose severe environmental and health risks, including water pollution and eutrophication. This study explores the use of ammonium polymer as an adsorbent and the influence of pH in the adsorption process as a promising technique for removing nitrate ions from bioethanol waste. Based on the analysis that has been carried out, the optimal pH for adsorption of nitrate ions is around 9, where the removal efficiency (%RE) reaches 98.43% and the adsorption capacity (Qe) is 24.86 mg/g. These experiments show that the Freundlich model, with a heterogeneity factor (n) of 1.0947 and a Freundlich constant (KF) of 1.92 x 10³ units, provides the best fit to the adsorption data, indicating a heterogeneous adsorption process with a strong affinity for nitrate ions.